Observaciones fitogeográficas en un valle transversal del semiárido chileno - Quintanilla, Victor G. (Investigaciones Geográficas: Una mirada desde el sur, 1979)
The altitudinal distribution of the vegetation aproximately in the 30 degree of the southern latitude, namely that of the basin of the river Elqui between 100 and 3.000 meters has been analysed. Three different principal altitudinal zones can be recognised: the mountain, the subandine and the andine level. Each zone has characteristic species. The physiognomy is strongly adapted to the environmental conditions of each zone. The mountain level still conserve a number of sclerophyllous evergreen trees representatives tipics from valleys and lowland (Lithraea caustica, Quillaja saponaria and Geoffroea decorticans, Prosopis Chilenis). In the subandine level the trees are the predominent plants occuring in groups and present a number of new exponents (Kageneckia spp., Colliguaya spp. Adesnia spp. etc.). In the andine level scrubs and herbs asociated with grass and perennial gramineus are predominant, forming small patches. It is worth noting at present, the anthropological action zone by the felling of trees, mining, grazing and agricultural effects.